2022
DOI: 10.3390/biomedicines10020262
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Acute Kidney Injury after Allogeneic Stem Cell Transplantation: A Prospective Study

Abstract: (1) Background: Acute kidney injury (AKI) is a serious complication of hematopoietic stem cell transplantation (HSCT). (2) Methods: The aim was to identify the incidence, severity, and risk factors for AKI during the first 100 days after allo-HSCT; we performed a prospective observational study on 135 consecutive patients. (3) Results: The mean age was 38.3 ± 11.9 years (50.6% females), AKI developed in 93 patients (68.9%), the median time of appearance was 28 days, and the mean serum creatinine at the time of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…In our study, 59.1% of patients undergoing HSCTs developed AKI as defined by the KDIGO classification considering both creatinine and urinary output criteria in the first 100 days after HSCT. This cumulative incidence is in the range of recent studies (49.2-68.9%) that consider KDIGO classification-either by creatinine criteria alone [12,14,18] or by both creatinine and urinary output criteria [15,16] in populations with different hematologic malignancies undergoing HSCTs.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In our study, 59.1% of patients undergoing HSCTs developed AKI as defined by the KDIGO classification considering both creatinine and urinary output criteria in the first 100 days after HSCT. This cumulative incidence is in the range of recent studies (49.2-68.9%) that consider KDIGO classification-either by creatinine criteria alone [12,14,18] or by both creatinine and urinary output criteria [15,16] in populations with different hematologic malignancies undergoing HSCTs.…”
Section: Discussionmentioning
confidence: 81%
“…These same studies consistently associated AKI in the first 100 days after HSCT with lower overall survival-Kanduri et al (2020) published a meta-analysis [13] showing pooled odds ratios of 3-month mortality and 3-year mortality among patients undergoing HSCT with AKI were 3.05 (95% CI 2.07-4.49) and 2.23 (95% CI 1.06-4.73), respectively, with higher mortality in more severe stages. Also, Gutierrez et al [14] and Andronesi et al [18] found an association between AKI in allogeneic HSCTs and progression to CKD in HSCTs. These findings reinforce the importance of identifying patients at risk to implement prevention measures and early approach.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…1). Among included studies, four were prospective and 16 were retrospective [10, 11, 1330]. A total of 4,378 patients who underwent HSCT were included in the 20 studies, including 2,219 and 2,159 patients with and without AKI, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have revealed that some risk factors, such as myeloablative conditioning (MAC), sinusoidal obstruction syndrome (SOS), and allogeneic HSCT, contribute to AKI [10, 11]. However, the risk factors correlated with AKI after HSCT remain unclear.…”
Section: Introductionmentioning
confidence: 99%